'Throughout my life I've had people walk all over me': Trauma in the lives of violent men. Issue 4 (November 2017) - Ellis, Anthony; Winlow, Simon; Hall, Steve
This article presents original qualitative data gathered during prolonged ethnographic fieldwork with violent men in deindustrialised communities in the north of England. The data are used as an empirical platform for a theoretical exploration of the symbolism and subjectivising influences of traumatic life experiences in these men's biographies. The article concludes by making the tentative suggestion that there is a complex and mediated causal link between traumatic experience and a deep subjective commitment to aggression and violence in adulthood.